Ambient art: Creative information representation - Beale, Russell (Human Technology, 2007)
Ambient art is the aesthetic presentation of information, using artistic techniques to achieve a pleasing image that also contains hidden depths, where exposure to it over time allows a viewer to understand something about the information sources that it represents. This paper reviews the artistic and computational background of ambient systems, and presents two case studies of systems developed by our research team, from their initial design to the experiences of the people encountering them. The first case presents a photo mosaic of images based on the news headlines coupled with a structured picture based on the weather; the second presents stylistic perspectives on activity in a public space. Both are evaluated and demonstrate that different forms of aesthetically pleasing displays can convey information to viewers.